Social exclusion modulates dual mechanisms of cognitive control: Evidence from ERPs. Issue 10 (3rd June 2020) - Xu, Mengsi; Li, Zhiai; Qi, Senqing; Fan, Lingxia; Zhou, Xiaolin; Yang, Dong
Abstract: Many studies have investigated how social exclusion influences cognitive control but reported inconsistent findings. Based on the dual mechanisms of control framework, this study investigated how social exclusion influences proactive and reactive modes of control (Experiment 1) and the underlying mechanisms (Experiment 2). The Cyberball game was used to manipulate social exclusion. Eighty‐six female participants (about 40 for each experiment) performed cognitive control tasks while event‐related potentials were recorded. In Experiment 1, an AX Continuous Performance Task (AX‐CPT) was adopted to differentiate between proactive and reactive control. Results showed that social exclusion weakened proactive control but enhanced reactive control, as reflected by the weaker proactive control indicators (i.e., P3b and CNV), but strengthened reactive control indicators (accuracy and N2) in excluded individuals. More importantly, in Experiment 2, through varying in whether task cues were available before or after target onset in a cued‐flanker task, we further manipulated the possibility of engaging proactive control, and found the weakened proactive control could be attributed to both impaired cognitive ability and lowered motivation to engage proactive control in excluded individuals. Together, these results provide insight on how social exclusion influences cognitive control and suggest promising implications for designing effective interventions to relieve the negative impact of social exclusion.